Participatory Rural Appraisal of Basic Needs Deprivation among Rural Dwellers of Borno State, Nigeria - Yusuf, R. O (Asian Journal of Agriculture and Rural Development, 2014)
Inadequacy of environmental and infrastructural resources to satisfy basic needs results in deprivation among rural people which in most cases, rapid rural appraisal and other traditional survey methods rarely adequately capture. This paper employs therefore employs participatory rural appraisal (PRA) techniques to analyse these phenomena in Borno state. The objectives are to determine the seasonality of basic needs deprivation, analyse the triggers of need deprivation, and, assess the coping strategies for deprivation. PRA techniques employed are Seasonal Calendar and Force Field Analysis and 300 systematically selected participants from 9 local government areas were the study frame. The findings are that basic need deprivation is an outcome of environmental scarcities, resource capture, and failure of socioeconomic infrastructure. Episodic drought, flood, and conflict over resources triggers loss of farm harvest and livestock hence food, income and other needs there from. The coping strategies include wild food foraging, migratory fishing and praying to God which lead to the conclusion that basic needs satisfaction among the studied rural dwellers in Borno state is below societal expectations. Recommendations for improvement were proffered.